Rancang Bangun Aplikasi Sistem Informasi pada Klinik Kesehatan Kucing Berbasis Android - Yogi Husien Rosidi (Jurnal Jaringan Telekomunikasi, 2017)
Animal clinics have inpatient services in the form of a quarantine room if inpatient animals need intensive examination, but the development of animals is in the form of ambulatory medical records that are not communicative and are still manual so that these ambulatory medical records are only stored at the PKH-UB Animal Clinic. The purpose of this research is to design an information system application to help clinics and patients based on android so that later the ambulatory medical record can be communicative. And also create a monitoring system for hospitalized animals so that patients can see through smartphones. The results of the tests carried out, based on distributed questionnaires, the results of the implementation of the application for ease of use stated that 75.375% were valid and the application was feasible and good to use, and the display on the IP Camera for inpatient monitoring facilities with WLAN infrastructure topology obtained an average delay of 0, 18 seconds for movement of the application display on android.